2012
DOI: 10.1111/j.1442-2050.2011.01311.x
|View full text |Cite
|
Sign up to set email alerts
|

Vascular conditioning of the stomach before esophageal reconstruction by gastric interposition

Abstract: Gastric interposition with intrathoracic or cervical esophagogastrostomy is currently the preferred operation for reconstruction after esophagectomy. Anastomotic leaks however result from poor vascular supply to the proximal stomach. They are responsible for significant morbidity and mortality. 'Ischemic conditioning' of the interposed stomach has been proposed as a technique where the 'delay phenomenon' aims at improving the microcirculation of the gastric conduit and preventing anastomotic leakage. Experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 70 publications
(269 reference statements)
0
14
0
Order By: Relevance
“…A recent review on the topic of microcirculation following ischemic conditioning found ten studies that demonstrated improved circulation at the gastric conduit tip following ischemic conditioning. 19 There were a number of different methods used to assess the 19 For our study, we elected to perform microvessel counts of postoperative biopsy specimens at the conduit tip. This method was well suited for our purposes, because it provided a quantitative measurement, did not add an additional step to the operative procedure, and allowed us to take advantage of our database of available surgical specimens.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…A recent review on the topic of microcirculation following ischemic conditioning found ten studies that demonstrated improved circulation at the gastric conduit tip following ischemic conditioning. 19 There were a number of different methods used to assess the 19 For our study, we elected to perform microvessel counts of postoperative biopsy specimens at the conduit tip. This method was well suited for our purposes, because it provided a quantitative measurement, did not add an additional step to the operative procedure, and allowed us to take advantage of our database of available surgical specimens.…”
Section: Discussionmentioning
confidence: 88%
“…As a result, a number of techniques have been devised to improve blood flow to the gastric conduit. These methods include anastomosing donor vessels to the gastric circulation, use of a pedicled omental flap around the anastomosis, phlebotomy through the short gastric veins to decrease vascular congestion, and delayed anastomosis with gastric ischemic conditioning . The basis of ischemic conditioning is that perfusion to conduit tip can be enhanced by ligation of select vessels to the stomach prior to esophagogastrostomy, allowing new microcirculation to develop to the gastric fundus at the site of the anastomosis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations